Pengembangan E-LKPD Berbasis Inkuiri Terbimbing Materi Struktur Bumi dan Perkembangannya Untuk Memfasilitasi Kemampuan Berpikir Kreatif Siswa Pada Kurikulum Merdeka - Malahayati, Ghina Aghniah; Nulhakim, Lukman; El Islami, R. Ahmad Zaky (PendIPA Journal of Science Education, 2025)
Teaching materials are one of the important learning supports. Therefore, the teaching materials used by teachers must be interactive and creative. The purpose of this study was to produce valid E-LKPD teaching materials and to describe the results of student responses to teaching materials in the form of E-LKPD based on guided inquiry on the material of earth structure and its development to facilitate students' creative thinking skills in the independent curriculum. The research method used in this study, namely the Research and Development (R&D) method according to Thiagarajan (1974) which has been adjusted to the needs of researchers, namely only up to the dissemination stage, up to the limited trial stage only. The research instruments used in this study, namely the Science Education expert validation sheet which had previously been validated by instrument experts and student response questionnaire sheets. Data analysis in this study was carried out descriptively quantitatively and qualitatively. The research data obtained the results of the validity level of the development of E-LKPD teaching materials based on guided inquiry on the material of the earth's structure and its development with an assessment by a validator of science education experts obtained a percentage of 88.36% and was included in the category of "Very Valid". For the results of student responses to E-LKPD, the percentage was 88% with the category of "Very Good". So that the use of E-LKPD teaching materials based on guided inquiry on the material of the earth's structure and its development can facilitate students' creative thinking skills and can be used for science learning.